The Yugoslav „special war” against the backdrop of the concept and doctrine of universal national defense of the SFRY – theory and evolution - Kuś, Małgorzata (Balcanica Posnaniensia. Acta et studia, 2025)
This article is an attempt to analyze and systematize views on the Yugoslav concept of special warfare, known as “specijalni rat”, which is an integral part of the doctrine of universal national defense. Its aim is to present the origins, evolution, and legal and theoretical foundations of this concept against the background of doctrinal and systemic solutions implemented within the framework of the SFRY's universal national defense system. This has made it possible to systematize the current state of knowledge in this area and to emphasize the importance and uniqueness of the solutions applied in the field of defense policy in the former Yugoslavia, which were developed in response to actions (including asymmetric ones, to use contemporary nomenclature) on the part of the Croatian and Serbian political opposition and countries hostile to the Yugoslav state during the Cold War. This article presents the origins of the „special war” in the context of the Cold War and Yugoslavia's unique geopolitical position, taking into account the place and role of the Yugoslav People's Army, the security services, and the Territorial Defense in implementing its objectives. Particular emphasis is placed on its psychological, political, intelligence, and paramilitary dimensions, as well as on the legal and social mechanisms that were supposed to ensure the state's resilience to external and internal threats.